Natural infection of Viola cornuta (Violaceae) with Cucumber mosaic virus, subgroup I - Arneodo Larochette, Joel Demián (2005)
Plants of Viola cornuta displaying typical virus symptoms were observed during spring 2003 in a plant nursery in Córdoba, central Argentina. Electron microscopic examinations of symptomatic leaf samples revealed the presence of isometric virus-like particles about 30 nm in diameter. Subsequent serological analysis allowed the identification of the pathogen as a subgroup I strain of Cucumber mosaic virus (CMV). These results were confirmed by antigen capture - reverse transcription - polymerase chain reaction with specific CMV primers, and digestion with a restriction enzyme. This is the first report of CMV infecting V. cornuta in Argentina.